Generalized stochastic derivatives on a space of regular generalized functions of Meixner white noise - Kachanovsky, N. A. (Methods of Functional Analysis and Topology, 2008)
We introduce and study generalized stochastic derivatives on a Kondratiev-type space of regular generalized functions of Meixner white noise. Properties of these derivatives are quite analogous to the properties of the stochastic derivatives in the Gaussian analysis. As an example we calculate the generalized stochastic derivative of the solution of some stochastic equation with a Wick-type nonlinearity.